Significance of Very‐High‐Frequency Oscillations (Over 1, 000Hz) in Epilepsy. Issue 2 (30th June 2015) - Usui, Naotaka; Terada, Kiyohito; Baba, Koichi; Matsuda, Kazumi; Usui, Keiko; Tottori, Takayasu; Mihara, Tadahiro; Inoue, Yushi
<x xml:space="preserve">Abstract</x> Objective We previously reported ictal very‐high‐frequency oscillations (VHFO) of 1, 000 to 2, 500Hz recorded by subdural macroelectrodes using a 10‐kHz sampling rate. The purpose of this study was to clarify the clinical significance of ictal VHFO in neocortical epilepsy. Methods This study included 13 patients with neocortical epilepsy who underwent subdural electrode implantation and had at least 1 seizure recorded at a 10‐kHz sampling rate and were followed for more than 2 years postoperatively. Extent of resection was determined considering the seizure onset zone (SOZ) and irritative zone, structural lesion, and functional areas. Areas showing VHFO and those with HFO were not taken into consideration. The presence or absence of VHFO (>1, 000Hz), HFO (200–1, 000Hz) and SOZ, and completeness of resection of these areas were compared with postoperative seizure outcome. Results Seven patients had favorable (Engel class Ia) and 6 had unfavorable outcomes (other classes). VHFO was recorded in 6 of 7 patients with a favorable outcome. On the contrary, VHFO was recorded in only 1 of 6 patients with unfavorable outcome. The presence of VHFO was significantly associated with favorable outcome. VHFO was recorded on a limited number of electrodes, and VHFO‐generating areas were resected completely, whereas HFO‐generating areas and/or SOZ were not always resected completely in both favorable and unfavorable outcome groups. Interpretation The presence of ictal VHFO may be predictive of favorable outcome. Ictal VHFO may be a more specific marker than ictal HFO or SOZ for identifying the core of epileptogenic zone. Ann Neurol 2015;78:295–302